2019
DOI: 10.1016/j.neuroimage.2019.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Internal noise in contrast discrimination propagates forwards from early visual cortex

Abstract: Human contrast discrimination performance is limited by transduction nonlinearities and variability of the neural representation (noise). Whereas the nonlinearities have been wellcharacterised, there is less agreement about the specifics of internal noise. Psychophysical models assume that it impacts late in sensory processing, whereas neuroimaging and intracranial electrophysiology studies suggest that the noise is much earlier. We investigated whether perceptually-relevant internal noise arises in early visu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…It has also been suggested that monocular noise might be increased in the affected eye of individuals with amblyopia [43]. Finally, we have recently shown [44] using a contrast discrimination paradigm that EEG and MEG data are consistent with both an early (~100ms post stimulus onset) noise source in low level visual areas, and a later noise source in more frontal and parietal brain areas, both of which affect perceptual decisions. All of these results are therefore consistent with an early monocular source of internal noise, as included in our model, but do not preclude the addition of later sources of noise which we do not consider here.…”
Section: Discussionsupporting
confidence: 59%
“…It has also been suggested that monocular noise might be increased in the affected eye of individuals with amblyopia [43]. Finally, we have recently shown [44] using a contrast discrimination paradigm that EEG and MEG data are consistent with both an early (~100ms post stimulus onset) noise source in low level visual areas, and a later noise source in more frontal and parietal brain areas, both of which affect perceptual decisions. All of these results are therefore consistent with an early monocular source of internal noise, as included in our model, but do not preclude the addition of later sources of noise which we do not consider here.…”
Section: Discussionsupporting
confidence: 59%
“…We next analyzed event-related potentials (ERPs) from a contrast discrimination experiment reported by Vilidaite, Marsh, and Baker (2019) , recorded using a 64-channel EEG cap. The stimuli were sine wave gratings with a contrast of 50%, presented sequentially in pairs for 100 ms each, with an interstimulus interval of 400–600 ms.…”
Section: Eeg: Event-related Potentialsmentioning
confidence: 99%
“…As they put it: “That false alarms evoked more activity than misses indicates that activity in early visual cortex corresponded to the subjects’ percepts, rather than to the physically presented stimulus” (p. 414). Although not all neuroimaging studies have detected elevated neural signals in sensory pathways associated with false detection (e.g., Hulme, Friston, & Zeki, 2009; Mostert, Kok, & de Lange, 2015), many have (e.g., Pajani, Kok, Kouider, & De Lange, 2015; Ress & Heeger, 2003; Watkins, Shams, Tanaka, Haynes, & Rees, 2006; Vilidaite, Marsh, & Baker, 2019). In addition, still other neuroimaging studies have provided evidence that activity in higher (nonsensory) regions supports the false subjective experience of perception (e.g., Lloyd, McKenzie, Brown, & Poliakoff, 2011; similar conclusions about the role of higher brain regions were reached in single-unit work by de Lafuente & Romo, 2005, 2006).…”
Section: The Neuroscience Of Signal Detection Theory (1980s–present Day)mentioning
confidence: 99%